Orygenes i hebrajski tekst Pisma Świętego - Królikowski, Janusz (Vox Patrum, 2018)
Origen is the exegete and Old Christian writer whose influence on the understanding of the Bible has always been determinative. Undoubtedly, for ecclesiastical reasons he deemed the Septuagint superior and regarded it as the Christian Old Testament. He thought highly of Hebrew text as well, which he often used for his research. An expression of this belief was among others the Hexapla worked out by Origen, which can be regarded as an exceptional manifestation of esteem towards the Old Testament and its Hebrew version. Origen’s attitude towards the Bible can be characterized by two approaches: on the one hand it is the ecclesiastical approach which gives the first place to the text commonly accepted in the Church namely the Septuagint, but on the other hand he is open to every other text Hebrew or Greek, trying to understand it and take it into account in his commentary.